2016
DOI: 10.1088/1674-1137/40/8/089001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental study of PbWO 4 /EPDM and Bi 2 WO 6 /EPDM for the shielding of γ -rays

Abstract: Abstract:The MCNP5 code was employed to simulate the γ-ray shielding capacity of tungstate composites. The experimental results were applied to verify the applicability of the Monte Carlo program. PbWO4 and Bi2WO6 were prepared and added into ethylene propylene diene monomer (EPDM) to obtain the composites, which were tested in the γ-ray shielding. Both the theoretical simulation and experiments were carefully chosen and well designed. The results of the two methods were found to be highly consistent. In addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In an experimental research on WO 3 /Epoxy against high-energy sources, tungsten trioxide micro-particles were tested via practical experiments with 60 Co irradiation. In the mentioned study, researchers emphasized on the necessity to preserve the mechanical and thermal properties of the composite, while increasing the weight percentage while showing that a 50% weight concentration (similar to the current research) would maintain the mechanical and thermal properties to a great degree in addition to being radiation absorbent [7].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In an experimental research on WO 3 /Epoxy against high-energy sources, tungsten trioxide micro-particles were tested via practical experiments with 60 Co irradiation. In the mentioned study, researchers emphasized on the necessity to preserve the mechanical and thermal properties of the composite, while increasing the weight percentage while showing that a 50% weight concentration (similar to the current research) would maintain the mechanical and thermal properties to a great degree in addition to being radiation absorbent [7].…”
Section: Discussionmentioning
confidence: 88%
“…Meanwhile, various studies have shown that composites containing micro- and nanoparticles of high-Z fillers dispersed in a conformable polymer matrix can be used to design high-energy radiation shields as an alternative to traditional shielding material [2,7]. polymeric matrix with proper filler have shown to have unique properties, due to large surface-area-to-volume ratio of fillers in the polymer matrix, and it is expected that the overall weight of a shield will decrease while its absorption/attenuation abilities improves.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is particularly evident for the data where μ m drops from 4.589-0.020 cm 2 g −1 , 6.311-0.021 cm 2 .g −1 , 8.350-0.022 cm 2 .g −1 and 10.804-0.023 cm 2 produces a considerable drop in the μ m values for all analyzed samples [43]. As a result, photon value enrichment resulted in a dramatic drop in the interaction cross-section, which was accompanied by a corresponding decrease in photon-electron interactions and μ m values [45]. As presented in table E 1 is blamed for the exponential decline.…”
Section: Shielding Properties Of the Prepared At 100-2x Pb X Cd X Nan...mentioning
confidence: 94%
“…The particle size of the filler materials has been proven in several investigations to affect the attenuation of photons with energies greater than 1 MeV [42,43]. While this is going on, numerous studies have shown that composites made of high-atomic number filler micro-and nanoparticles dispersed in conformable polymer or clay matrices can be used to create high-energy radiation shields that can be used as an alternative to conventional shielding material [33,34,44,45]. According to the results of these investigations, glassy materials can exhibit greater shielding properties when oxides of a smaller size are doped into them [46].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the role of multi-layered materials in radiation protection is undeniable. Therefore, several authors have published reports, for example, for studying the radiation shieding of multi-layer metal/polymer composites [3], polymer-composite materials [2], metal multi-layered shields [6,10], light multi-layered shields [11], multi-layered shields containing poly boron and Borax mixed ilmenite-magnetic concrete [12], multi-layers of PbWO4/EPDM and Bi2WO6/ EPDM [13], multi-layer x-ray absorbers [14] and multi-layer structures for space proton radiation protection [15].…”
Section: Introductionmentioning
confidence: 99%